Pengaruh Kualitas Pelayanan Terhadap Kepuasan Lansia (Studi Kasus di Desa Gledug Kabupaten Blitar) - Fandi Sudiasmo; Novi Dwi Rengganis (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2021)
Over time, the human age will continue to increase chronologically. With increasing age there is a decrease in several vital functions in the human body. For example, such as decreased hearing function, blurred vision, and weakened physical strength. This is a fact experienced by the elderly or commonly referred to as the elderly. At this time the elderly have been provided with elderly posyandu service facilities that help the elderly in dealing with their health problems. From these thoughts, this research will explore the influence of posyandu cadre service quality on elderly satisfaction and the obstacles and barriers to achieving that satisfaction. Based on the research obtained from the results of the SPSS simultaneous effect test (F-test), it shows that the T-test value is T-count (3,220)> T-table (2,007) and the significance is 0.002 <0.05, so H0 is rejected and H1 is accepted. From this value, it is concluded that service quality has an influence on satisfaction. This shows that there is a significant relationship between the service quality of cadres and the satisfaction of the elderly. The approach used is quantitative descriptive method. The outcomes acquired show that the degree of satisfaction of the elderly in receiving services provided by cadres is good. This is influenced by the cadres' friendliness, the sense of politeness seen by the elderly and the responsibility of cadres in providing services that are well received by the elderly. From the results of the discussion, there are several obstacles that affect satisfaction. So that services should be improved again to accomplish to achieve elderly satisfaction.